Fertilização mineral em Pinus taeda L.: crescimento, variáveis fisiológicas e níveis críticos de fósforo - Kulmann, Matheus Severo de Souza (2023)
Pinus taeda L. plantations in subtropical regions of South America are located in highly weathered soils, with low natural fertility, especially those deficient in phosphorus (P). Thus, phosphate fertilization is necessary in plantations. However, the response of P. taeda to increased P levels in the soil, via fertilization, is still incipient. Thus, this Thesis aimed to evaluate the effect of mineral fertilization on P. taeda on growth, physiological variables and critical levels of P. For this, we wrote five Chapters (I, II, III, IV and V). In Chapter I we conducted a literature review seeking to describe the current importance of silvicultural practices, such as mineral fertilization, on the growth responses of P. taeda, and especially to know which nutrients have greater positive responses on the productivity of the plantations. In Chapter II, we investigated whether increased soil P levels influence the association with ectomycorrhizal fungi on morphological parameters of the shoot and roots, nutritional, biochemical, and physiological status of P. taeda. In Chapter III, we verified if the P omission decreases the P uptake by the plants and, thus, the P concentration in needless, limiting physiological and biochemical parameters, causing oxidative stress to the plants and, consequently, decreasing the growth of P. taeda. Finally, in Chapters IV and V, we propose critical levels (CL) and sufficiency range (SR) of P in needles and soil of young and adult P. taeda plantations, respectively, and relate them to plant productivity. The review showed that Pinus spp. plantations are adapted to acidic soils with low natural fertility. However, the plants have high dependence on strategies to increase the efficiency of nutrient uptake, such as mycorrhizal association. On the other hand, specific sites show positive responses to mineral fertilization, especially at low soil nutrient availability, such as P. We observed that increasing soil P provided an increase in P uptake and development of root surface area, volume, and length, enhanced by inoculation of ectomycorrhizal fungi, such as Pisolithus microcarpus. The increase of P within the plant increased the values of the variables related to the physiological apparatus. This increased the biomass production and growth of P. taeda. We found that P omission reduced soil P available and, consequently, roots P uptake and P concentration in needles, what took P. taeda to physiological stress, reducing photosynthetic efficiency and thus plant development. The CL of P in needles were 1.4 and 1.6 g P kg–1 for young and adult P. taeda plantations, respectively. The CL of P in soil was of 2.3 and 1.3 mg P dm–3 in young and adult P. taeda plantations, respectively. These results may contribute to ensure the nutritional balance of plants, with appropriate recommendations for phosphate fertilizers, reducing production costs and potential contamination of surface water adjacent to P. taeda plantations.